2010
DOI: 10.1073/pnas.1003124107
|View full text |Cite
|
Sign up to set email alerts
|

Rice pollen hybrid incompatibility caused by reciprocal gene loss of duplicated genes

Abstract: Genetic incompatibility is a barrier contributing to species isolation and is caused by genetic interactions. We made a whole genome survey of two-way interacting loci acting within the gametophyte or zygote using independence tests of marker segregations in an F 2 population from an intersubspecific cross between O. sativa subspecies indica and japonica. We detected only one reproducible interaction, and identified paralogous hybrid incompatibility genes, DOPPELGANGER1 (DPL1) and DOPPELGANGER2 (DPL2), by posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
192
4
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 165 publications
(209 citation statements)
references
References 45 publications
9
192
4
2
Order By: Relevance
“…Because the wild relatives of rice are adapted to different biogeographic ranges (Fig. 1a) and can tolerate many biotic and abiotic stresses [1][2][3][4][5][6] , they constitute an important reservoir for crop improvement. Strategies to harness such traits for crop improvement show clear promise, as exemplified by the introgression of bacterial blight resistance (Xa21) from the wild species Oryza longistaminata 7 .…”
mentioning
confidence: 99%
“…Because the wild relatives of rice are adapted to different biogeographic ranges (Fig. 1a) and can tolerate many biotic and abiotic stresses [1][2][3][4][5][6] , they constitute an important reservoir for crop improvement. Strategies to harness such traits for crop improvement show clear promise, as exemplified by the introgression of bacterial blight resistance (Xa21) from the wild species Oryza longistaminata 7 .…”
mentioning
confidence: 99%
“…In plants, it is not yet clear how often natural selection is a primary driver of hybrid incompatibilities. In several cases, hybrid dysfunction is caused by divergence at duplicate genes in a manner consistent with the action of random genetic drift (Bikard et al 2009;Mizuta et al 2010;Yamagata et al 2010). On the other hand, it was recently shown that a hybrid lethality allele has risen to high frequency in a population of M. guttatus due to linked selection for an allele that confers copper tolerance (Wright et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In Arabidopsis and rice, genetic incompatibilities have been mapped to duplicate genes that carry loss-of-function alleles in alternate copies (Bikard et al 2009;Mizuta et al 2010;Yamagata et al 2010), suggesting that divergence among paralogs via mutation and genetic drift might cause postzygotic reproductive isolation (Lynch and Force 2000). There are also hints that natural selection can contribute to the spread of incompatible alleles within populations and species.…”
mentioning
confidence: 99%
“…Classical two-locus BDM interactions between differentially inactivated duplicated genes appear to cause pollen sterility in hybrids between Oryza sativa and O. glumaepatula (Yamagata et al 2010) and between the two O. sativa subspecies japonica and indica (Mizuta et al 2010). In both of these BDM interactions, a particular combination of alleles present at the two loci is deleterious at the haploid stage, leading to the production of deficient pollen grains in the hybrid plant.…”
mentioning
confidence: 99%